1991
DOI: 10.1111/j.1600-0447.1991.tb03163.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression‐related disturbances in mitogen‐induced lymphocyte responses and interleukin‐1β and soluble interleukin‐2 receptor production

Abstract: In an attempt to delineate the pathophysiology underpinning the previously reported blunted lymphocyte responses to mitogenic stimulation in depressed patients, we measured the following immune variables in 28 depressives and 10 healthy controls: pre- and postdexamethasone (1 mg orally) lymphocyte responses to various mitogens, such as phytohaemagglutinin (PHA), and the PHA-induced accumulation of interleukin-1 beta (Il-1 beta) and soluble interleukin-2-receptors (sIl-2Rs) in culture supernatants. In the prede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(115 citation statements)
references
References 42 publications
3
108
0
4
Order By: Relevance
“…Human studies have indicated that dietary supplementation with EPA and DHA results in suppression of IL-1, IL-2, IL-6 and TNF-a production by monocytes (Calder, 1997). Given that cytokines such as IL-1, IL-2, IL-6 and TNF-a have been reported to relate positively to depression (Maes et al, 1991;Maes, 1995;Hestad et al, 2003), the observed inverse relationship between adipose tissue DHA and depression, in the present study, may be due to an inhibiting effect of DHA on the production of the particular cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have indicated that dietary supplementation with EPA and DHA results in suppression of IL-1, IL-2, IL-6 and TNF-a production by monocytes (Calder, 1997). Given that cytokines such as IL-1, IL-2, IL-6 and TNF-a have been reported to relate positively to depression (Maes et al, 1991;Maes, 1995;Hestad et al, 2003), the observed inverse relationship between adipose tissue DHA and depression, in the present study, may be due to an inhibiting effect of DHA on the production of the particular cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it appears that depression may be associated with variations of either circulating cytokine levels (ie, cell signalling factors released from activated macrophages), or cytokine production from mitogenstimulated lymphocytes, including interleukin-2 (IL-2), soluble IL-2 receptors (sIL-2R), IL-1␤, IL-1 receptor antagonist (IL-1Ra), IL-6, soluble IL-6 receptor (sIL-6R), and ␥-interferon (IFN). [209][210][211][212][213][214][215][216] While there have been reports that the elevated levels of IL-1␤, IL-6 and ␣1-acid glycoprotein normalized with antidepressant medication, 217 the unregulated production of sIL-2R, IL-6 and sIL-6R was not attenuated with antidepressant agents, leading to the suggestion that the latter factors may be trait markers of the illness. 208 Although severity of depressive illness is likely fundamental in determining cytokine levels, 208 the possibility cannot be ignored that chronic depression (or chronic stress) may induce cytokine changes to a greater extent than those observed following acute episodes (as in the case of major depression).…”
Section: Cytokines and Depressive Illnessmentioning
confidence: 99%
“…Nevertheless, mild chronic inflammation [1,6,7] is only one very general concept in depression and describes its pathophysiology only superficially [8]. Since 1990, other and sometimes more important immune-related pathways were discovered, e.g.…”
Section: Inflammation Is Not the Only Drug Target In Depressionmentioning
confidence: 99%
“…Moreover, depression is characterized by immune-serotonin interactions, including activation of indoleamine 2,3-dioxygenase (IDO) with increased levels of tryptophan catabolites (TRYCATs) and lowered levels of tryptophan [20][21][22]; immune-endocrine interactions, including cytokine-associated glucocorticoid resistance [6,9]; and immune-metabolic (in particular lipids) interactions, including inverse associations between immune activation and lowered high density cholesterol, 3 polyunsaturated fatty acid (PUFAs) levels and the reverse cholesterol transport [11,23]. Interestingly, animal depression models based on psychosocial stress show that depression-like behaviors are associated with activated immune-inflammatory and oxidative and nitrosative stress (O&NS) pathways [24,25].…”
Section: Inflammation Is Not the Only Drug Target In Depressionmentioning
confidence: 99%